Religious Moderation Education in Building Social Harmony From The Perspective Of The Qur’an Surah Al-Hujurat Verse 13 - Nova Liana; Rachmat Mulia; Meilisa Sajdah; Muhammad Mufid Zardi; Liana Febrianti; Edi Saputra; Tri Hariyati; Khairunesa Isa (AFKARINA: Jurnal Pendidikan Agama Islam, 2025)
This study examines religious moderation education in building social harmony from the perspective of QS. Al-Hujurat verse 13 as a response to the increasing phenomena of intolerance, social conflict, and identity polarization in multicultural societies, particularly in the digital era characterized by the uncontrolled flow of information without value filters. This research employs a qualitative approach using the library research method, with data sources derived from the Qur’an, tafsir books, and relevant scientific literature, which are analyzed using content analysis techniques. The findings reveal that QS. Al-Hujurat verse 13 contains fundamental values such as ta’aruf (mutual understanding), human equality, and the rejection of superiority based on ethnicity, race, and social status. These values serve as the foundation for developing a humanistic, inclusive, and character-oriented education aimed at fostering moderate attitudes. The study concludes that religious moderation education plays a strategic role in shaping tolerant character, acting as a filter against narratives of intolerance in digital spaces, and strengthening social harmony. Therefore, the integration of Qur’anic values into education becomes essential in realizing a peaceful, inclusive, and civilized society.